Does Innovation Play a Role in the Relationship Between Corporate Social and Financial Performance? A Systematic Literature Review - Fadwa El FALLAHI; Abdelmajid Ibenrissoul; Adil EL AMRI (Goodwood Publishing, 2022)
Purpose: This research aims to provide a comprehensive knowledge map of the intellectual structure of the field of study on the role of innovation in shaping the social and financial performance link. Research methodology: Systematic literature review using the SALSA (Search, Appraisal, Synthesis, and Analysis) Method based on a 10-year data set (2012-2021) from the “Google Scholar” database. Results: The findings point to the existence of a positive influence of innovation in linking Corporate Social Performance to firm Financial Performance and reveal the existence of five themes in the research, specifically complementarity between Corporate Social Responsibility and innovation, the special case of small and medium-sized enterprises, and the context of emerging countries. Also, we highlight a lack of research in this field and the theoretical, design, and methodological limitations of previous studies. Limitations: The primary limitation of this study is the small number of studies that address the research question addressed by this systematic literature review, which was generated by the research protocol. Contribution: The study suggests avenues for future research to address the previous shortcomings. Particularly, identifying the condition effects through which innovation may affect the studied relationship.